Detection of Mycobacterium tuberculosis DNA on the oral mucosa of tuberculosis patients - Wood, Rachel C.; Luabeya, Angelique K.; Weigel, Kris M.; Wilbur, Alicia K.; Jones-Engel, Lisa; Hatherill, Mark; Cangelosi, Gerard A. (Scientific reports, 2015)
Diagnosis of pulmonary tuberculosis (TB) usually includes laboratory analysis of sputum, a viscous material derived from deep in the airways of patients with active disease. As a diagnostic sample matrix, sputum can be difficult to collect and analyze by microbiological and molecular techniques. An alternative, less invasive sample matrix could greatly simplify TB diagnosis. We hypothesized that Mycobacterium tuberculosis cells or DNA accumulate on the oral epithelia of pulmonary TB patients and can be collected and detected by using oral (buccal) swabs. To test this hypothesis, 3 swabs each were collected from 20 subjects with active pulmonary TB and from 20 healthy controls. Samples were tested by using a polymerase chain reaction (PCR) specific to the M. tuberculosis IS6110 insertion element. Eighteen out of 20 confirmed case subjects (90%) yielded at least 2 positive swabs. Healthy control samples were 100% negative. This case-control study supports past reports of M. tuberculosis DNA detection in oral swabs. Oral swab samples are non-invasive, non-viscous and easy to collect with or without active TB symptoms. These characteristics may enable simpler and more active TB case finding strategies.